Cataract in rural Myanmar: prevalence and risk factors from the Meiktila Eye Study. Issue 9 (23rd July 2008) - Athanasiov, P A; Casson, R J; Sullivan, T; Newland, H S; Shein, W K; Muecke, J S; Selva, D; Aung, T
Abstract : Aims: To determine the prevalence of and risk factors for cataracts in a rural region of central Myanmar. Methods: A cross-sectional, population-based survey of inhabitants ⩾40 years of age from villages of central Myanmar; 2076 participated, and 2044 (82.3%) had an examinable lens in at least one eye. Data recording included smoking history, occupation, education level, betel-nut chewing, height and weight, and dilated lens assessment using Lens Opacities Classification System III grading: nuclear (⩾4), cortical (⩾2) and posterior subcapsular (⩾2) cataracts. Aphakic and pseudophakic eyes were included as operated cataracts for statistical analysis. Results: The prevalence of any cataract including operated eyes was 40.39% (95% CI 37.30 to 43.48%): 27.35% nuclear, 20.91% cortical and 11.34% posterior subcapsular cataracts. No significant association was found between cataract and betel-nut use, gender, smoking or outdoor occupation. The likelihood of all cataract types increased with age (multivariate analysis including operated eyes: OR 1.154, CI 1.13 to 1.18, p < 0.001). Low level of education and low body mass index were associated with nuclear cataracts. Large village size was associated with increased risk for nuclear cataract (OR 3.23, CI 1.989 to 5.250, p < 0.001) and decreased risk for cortical cataract (OR 0.20, CI 0.08 to 0.47, p < 0.001). Conclusions: The prevalence of cataract in rural Myanmar is similar to that in other developing Asian regions. Cataracts are strongly associated with increasing age, and are more common in those with lower education and lower body mass index.